Estudio del proceso de fabricación para obtener bloques huecos de hormigón para mamposteria con resistencia a la comprensión de 2,5 a 4 Mpa en la cuidad de Riobamba - Romero Aldás, Wilson Alfredo (2011)
The proposal about the study of the manufacturing process to obtain hollow concrete blocks for masonry, is based on the need for blocks that meet the minimum strength required , for which we rely on technical parameters, social, cultural and economic. For the elaboration of hollow blocks type B and D is performed a mortar dosage that achieves the resistances of 2.5 and 4 MPa, for dividing walls and self-supporting. The mixture of the amount of material obtained in the dosage (macadam and cement) is placed in the mold of vibro-presser machine in order to obtain blocks of 15x20x40 cm and 20x20x40 cm, the obtained block is transported to a place that provides the required technical conditions to cure for a period of 7 days, after which they are stored for an eventual sale.